2017
DOI: 10.21037/cco.2017.06.04
|View full text |Cite
|
Sign up to set email alerts
|

Rational combinations of immunotherapy for pancreatic ductal adenocarcinoma

Abstract: The complex interaction between the immune system, the tumor and the microenvironment in pancreatic ductal adenocarcinoma (PDA) leads to the resistance of PDA to immunotherapy. To overcome this resistance, combination immunotherapy is being proposed. However, rational combinations that target multiple aspects of the complex anti-tumor immune response are warranted. Novel clinical trials will investigate and optimize the combination immunotherapy for PDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Vaccines have been designed to generate a humoral/cellular immune response with the aim of stimulating the host immune system to recognize and eliminate tumor cells with specific effector and memory T cells. There are two major categories of tumor vaccines: whole cell vaccines and antigen-specific vaccines ( 289 ). A brief review on the different vaccines currently investigated for pancreatic cancer can be found in the publication by Skelton et al ( 290 ).…”
Section: Other Combination Strategies Exploiting Antigenicity/immunogmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccines have been designed to generate a humoral/cellular immune response with the aim of stimulating the host immune system to recognize and eliminate tumor cells with specific effector and memory T cells. There are two major categories of tumor vaccines: whole cell vaccines and antigen-specific vaccines ( 289 ). A brief review on the different vaccines currently investigated for pancreatic cancer can be found in the publication by Skelton et al ( 290 ).…”
Section: Other Combination Strategies Exploiting Antigenicity/immunogmentioning
confidence: 99%
“…Preclinical data suggested beneficial effects when two vaccination treatments were co-implemented, e.g., GVAX and CRS-207, a live-attenuated Listeria monocytogenes vaccine expressing the TAA mesothelin, in a sequential combination—a so-called prime/boost approach. The first vaccine was given to initiate or “prime” the immune system, and this immune response was then “boosted” following re-administration of antigen resulting in the induction of a synergistic enhancement of T cell induction and antitumor effect ( 289 ). Based on the preclinical data, a phase II trial (NCT01417000) was conducted resulting in the conclusion that heterologous prime/boost with Cy/GVAX and CRS-207 extended the survival of patients with pancreatic cancer, with minimal toxicity ( 294 ).…”
Section: Other Combination Strategies Exploiting Antigenicity/immunogmentioning
confidence: 99%
“…Despite numerous methods in PDAC treatment, including new chemotherapeutic agents, emerging immunotherapy, and advanced surgical skills, the long-term survival rate has not shown significant improvement over the past decade. There are few effective therapeutics that can extend the overall survival of patients with PDAC [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, PDAC represents an immune quiescent, so-called "cold" tumor that is not sensitive to immune checkpoint inhibitors (1). Therefore, PDAC also serves as an ideal model for studying how to overcome the resistance to immune checkpoint inhibitor treatment (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%